Maudhui's Tafsir Method in the Qur'an and Hadith on Maqasid Syariah for Economic Welfare in Indonesia - Ermita Zakiyah (Journal of Islamic Economics and Philanthropy, 2022)
Abstract Al-Qur'an Hadith has a significant position on law-making based on the existing sharia maqasid Sharia, because from this maqasid the law will follow what is punished. Indonesia has an Islamic majority position, it should be based on the maqasid sharia contained in the Al-Qurán and Hadith, including for its economic welfare, so the question arises about how to interpret the Al-Qurán and hadith against maqasid sharia for economic prosperity in Indonesia? research on the interpretation of the Al-Qurán using the maudhui and hadith methods has never been studied with the maqasid sharia study for economic welfare in Indonesia, so it is necessary to conduct a more in-depth study of the interpretation of the AL-Qurán and hadith related to maqasid sharia. The research method that will be used is library research, with primary sources from the Qur'an and Hadith, secondary sources in the form of interpretation and syarah Hadith by performing the maudhui method stages from Farmawi and authentic Muslim Bukhrori hadith which are then mapped to the Qur'an and Hadith. This research will produce literature that makes maqasid sharia references based on the Qur'an and hadith for economic prosperity in Indonesia. This research will also have implications for people's views about maqasid from the Qur'an and hadith as a whole so that the welfare of the Indonesian people can be achieved